Estimation of threshold distributions for market participation - Mattia Guerini; Patrick Musso; Lionel Nesta (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2020)
We develop a new method to estimate the parameters of threshold distributions for market participation based upon an agent-specific attribute and its decision outcome. This method requires few behavioral assumptions, is not data demanding, and can adapt to various parametric distributions. Monte Carlo simulations show that the algorithm successfully recovers three different parametric distributions and is resilient to assumption violations. An application to export decisions by French firms shows that threshold distributions are generally right-skewed. We then reveal the asymmetric effects of past policies over different quantiles of the threshold distributions.
Keywords: C40; D01; F14; 330; Parametric Distributions of Thresholds; Maximum Likelihood Estimation; Fixed Costs; Export Decision